(untitled) - Lary, Hal B. (New York, 1968)
A previously widely quoted study by Hal Lary (Imports of Manufactures from: Less Developed Countries) concluded that labour intensity should, under the postulates of the factor-proportions model, be useful for anticipating the future composition of LDC exports. In this paper, we empirically evaluate the utility of labour intensity as such a guide. As a first test recent changes in developing countries' market shares for Lary's labour intensive products are compared with those for other items. With few exceptions, the export performance for labour intensive goods was superior. Overall, the LDCs increased their market share for these products in spite of a generally declining competitive position in world trade. Separate (correlation) tests indicate that a direct relation exists between the degree of labour intensity of individual products and changes in developing countries' market shares. That is, the LDCs made the greatest gains in the most labour intensive products.
Keywords: Khu vực kém phát triển,Underdeveloped areas; Thương mại,Commerce